Context-agile encryption for high speed communication networks. - Pierson, Lyndon G.
Different applications have different security requirements for data privacy, data integrity, and authentication. Encryption is one technique that addresses these requirements. Encryption hardware, designed for use in high-speed communications networks, can satisfy a wide variety of security requirements if the hardware implementation is key-agile, key length-agile, mode-agile, and algorithm-agile. Hence, context-agile encryption provides enhanced solutions to the secrecy, interoperability, and quality of service issues in high-speed networks. Moreover, having a single context-agile encryptor at an ATM aggregation point (such as a firewall) reduces hardware and administrative costs. While single-algorithm, key-agile encryptors exist, encryptors that are agile in a cryptographic robustness sense, are still research topics.